Measuring the Angular Momentum of Supermassive Black Holes - Brenneman, Laura; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Measuring the spin distribution of supermassive black holes is of critical importance for understanding how these black holes and their host galaxies form and evolve over time, yet this type of study is only in its infancy.  This brief describes how astronomers measure spin in supermassive black holes using X-ray spectroscopy.   It also reviews the constraints that have been placed on the spin distribution in local, bright active galaxies over the past six years, and the cosmological implications of these constraints.  Finally, it summarizes the open questions that remain in this exciting new field of research and points toward future discoveries soon to be made by the next generation of space-based observatories.
I. Introduction on importance of black hole spin -- II. Description of spectroscopic techniques used to measure spin in AGN -- III. Review of current spin measurements -- IV. Implications for the growth of black holes and their host galaxies -- V. Future Directions.
Keywords: Astronomy; Astrophysics; Gravitation; Observations, Astronomical; Astronomy—Observations.; Astronomy, Astrophysics and Cosmology; Classical and Quantum Gravitation, Relativity Theory; Astronomy, Observations and Techniques